(untitled) (International Journal of Engineering and Computer Science, 2015)
In agriculture field, the current agricultural practices need to intensify the rate of food crop production for the rate of population growth with available resources. This paper describes the automated system to make effective utilization of water resources for agriculture and crop growth monitoring using GSM and Zigbee technology. Firstly, this system utilized rainwater from the harvest rainwater tank for irrigation and then bore well water has been used. The water use efficiency is increased in drip irrigation system by using soil moisture sensor, humidity sensor and temperature sensor. The signals from the sensors are coordinated by the microcontroller and transmitted to irrigation control centre (ICC) through Zigbee wireless radio communication. The optimized water use for an agriculture crops has been achieved in the ICC successfully. The growth status of the crop also monitored using IR transceiver. The device that can report data to the cultivator remotely and the system allow them to effectively control through GSM.